Hypertrophy of paravertebral muscles after epidural electrical stimulation shifted: A case report - Li, Sipeng; Rong, Hongtao; Hao, Zhenghao; Tan, Rui; Li, Haijun; Zhu, Tao (Frontiers in Surgery, 2022)
Epidural electrical stimulation (EES) has been used to improve motor function in patients with chronic spinal cord injury (SCI). The effect of EES on paravertebral muscles in patients with SCI has been unnoticed. We reported a case of paravertebral muscles hypertrophy after the electrode shifted in a patient with spinal cord injury. We also discussed possible mechanistic accounts for this occurs.